The role of work attitude and job involvement on the relationship between recruitment, selection criteria, and selection process with performance in government agencies: A proposed model - Md Kamar, Mohd Azrin Akmar; Musairah, Sharifah Khairol; Mahmud, Luqman (International Journal of Accounting, Finance and Business, 2025)
Despite increasing awareness of the need for fair recruitment and selection practices, biases persist within these processes. This study aims to identify the factors contributing to these biases, highlighting that 84% of candidates perceive recruitment methods as unfair (Vanderpal & Brazie, 2022). Furthermore, many managers lack accurate information about candidates before interviews, complicating effective human resource management. Existing research often overlooks the moderating roles of work attitudes (WA) and job involvement (JI) in this context. This study addresses this gap by exploring the relationship between human resource management practices and performance in government agencies, integrating WA and JI into a unified model. Doing so aims to provide actionable insights into how enhancing employee attitudes can improve performance outcomes in public sector organizations.